Meta Analysis on Rehabilitation Effect of Proprioception Training on Ankle Sprainof Athletes - Yuxiao CHEN; Jiaojiao LIU; Changsong Yi; Mengguang CHAI; Qing WANG; Lei JIANG (康复学报)
Objective:To explore the effects of proprioception training on the incidence of athletes' ankle sprains, dynamic neuromuscular control, postural stability and joint position perception.Methods:Data were searched from the databases of PubMed, Cochrane Library, EMbase, China National Knowledge Infrastructure(CNKI), Wanfang Database(Wangfang Data), Chinese Journal Full-text Database(VIP), China Biomedical Literature Database(CBMdisc).Athletes were included in the randomized controlled trials(RCTs)who were treated with proprioception training to improve the function of athlete's ankle joint.The retrieval time for each database was from the establishment of the database to December 31, 2019, and the references of related documents were traced.Two researchers independently searchered the literature, extracted data, and evaluated the quality of the literature.RevMan5.3 software was used to analyze the data.According to the systematic review manual provided by the Cochrane Collaboration Network, the continuous variables use mean difference(MD)and 95%confidence interval(CI)as indicators, and binary variables use risk ratio(RR)and 95%CI as indicators.The statistical heterogeneity was judged comprehensively by chi-square test(χ2test)and the Heterogeneity test(I2test).If P≥0.1 and I2≤50%, a fixed effects model would be used.In contrast, if P<0.1 or I2>50%, a random effects model would be used.Results:A total of 11 RCTs and 1 776 athletes were included.The results of Meta analysis showed that compared with the control group, the incidence of ankle sprains in the experimental group was significantly reduced after proprioceptive training[RR=0.61, 95%CI(0.41, 0.90), P=0.01]; compared with the control group, the posterolateral and posterior medical maximum extension distances of the experimental group increased significantly after proprioception training[MD=4.44, 95%CI(3.66, 5.23), P<0.00 001;MD=4.21, 95%CI(3.18, 5.24), P<0.00 001]and the difference was statistically significant;but there was no significant difference in the improvement effect of the anterior maximum extension distance, and the difference was not statistically significant(P>0.05).The postural sway of the affected ankle joint in the experimental group was significantly lower than that in the control group;the athletes in the experimental group had better position perception ability in the ankle joint plantar flexion, dorsiflexion, middle and lateral directions than the control group.Conclusion:Proprioceptive training can effectively reduce the incidence of athletes' ankle sprains, improve dynamic neuromuscular control, improve postural stability, and enhance ankle joint position perception, which is worthy of clinical application.However, the absolute effect is not yet clear, so large samples and high-quality randomized controlled trials are still needed to further verify the efficacy of proprioception training, so as to provide more reliable evidence-based evidence for clinical rehabilitation.